The X of X - Churchman, C. West (Management Science, 1963)
A featured presentation at the Ninth Annual International Meeting of The Institute of Management Sciences, jointly with the Econometric Society, at Ann Arbor, Michigan, September 11, 1962. “A unified science of management.” Is it a matter of faith or of enterprise? A unified science of management conceals the self-reflective paradox. Science is an organized activity. Hence it operates according to some managerial principles. A unified science of management implies a management of science: a science of science, a self-reflective science.